A Few Remarks on the Common Matrimonial Property Regime of the Community of Surplus: German-French Case - Keller, Konstantin
Discussions regarding the arrangement of spouses' ownership are currently unfinished. On February 4, 2010, Germany and France signed an international treaty with intention to standardize the matrimonial property regimes in Europe.